Teaching Industry Model for Improving Students' Critical Thinking Skills in Vocational Higher Education - Ana Rahmi; Dina Ampera; Nikmat Akmal; Mawaddah Azizah Sari W (Jurnal Pendidikan Terapan, 2026)
Critical thinking skills are among the essential competencies required by students to face the challenges of the 21st century and the demands of the industrial world. However, the critical thinking skills of students in the Cake Decoration course at the Culinary Education Study Program still need improvement through learning approaches that are relevant to industrial practices. This study aimed to analyze the implementation of the Teaching Industry model and its role in improving students’ critical thinking skills in the Cake Decoration course. The study employed a quantitative approach involving 67 students of the Culinary Education Study Program at Universitas Negeri Medan. Data were collected through observation, questionnaires, and documentation, and analyzed using descriptive statistics, correlation, and regression analysis. The findings revealed that the implementation of the Teaching Industry model was categorized as high and contributed positively to the learning process. Students’ critical thinking skills increased from 8.4% at the needs analysis stage to 92.3% at the field implementation stage. The results also indicated that the Teaching Industry model provided authentic learning experiences that encouraged students to analyze problems, make decisions, evaluate information, and develop solutions based on industrial contexts. These findings imply that the Teaching Industry model can serve as an effective learning strategy for enhancing critical thinking skills and strengthening the relevance of vocational higher education to industry needs. The novelty of this study lies in the integration of industrial-based learning practices into the Cake Decoration course to foster students’ critical thinking skills in vocational education.